2022
DOI: 10.2478/sjecr-2019-0078
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase 2 Val16Ala Polymorphism is Associated with Amiodarone-Associated Liver Injury

Abstract: Association of SOD2 V16A single-nucleotide polymorphism (rs4880) with drug hepatotoxicity were reported but relationships with amiodarone prescriptions remained unexplored. Research was an exploratory, controlled prospective clinical trial. Patients hospitalized and treated in Clinical Center in Kragujevac, Serbia (in year 2017) were divided into experimental (using amiodarone, having liver injury, n=29, 19 males, the mean age 66.8±10.4 years), control A (neither amiodarone use nor hepatotoxicity, n=29, 19, 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It has been reported that human peripheral blood mononuclear cells from the carriers of TT genotype of SOD2 produced more proinflammatory cytokines such as IL-1, IL-6, TNF-α and IFN-γ than those having the CC genotypes, which could affect the hepatocyte’s function. 23 The pathology of chronic hemolytic status among SCD patients is a major contributing factor to gall stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that human peripheral blood mononuclear cells from the carriers of TT genotype of SOD2 produced more proinflammatory cytokines such as IL-1, IL-6, TNF-α and IFN-γ than those having the CC genotypes, which could affect the hepatocyte’s function. 23 The pathology of chronic hemolytic status among SCD patients is a major contributing factor to gall stone formation.…”
Section: Discussionmentioning
confidence: 99%